Method for Recovery and Immunoaffinity Enrichment of Membrane Proteins Illustrated with Metastatic Ovarian Cancer Tissues. (12th July 2012) - Schneider, Luke V.; Likhte, Varsha; Wright, William H.; Chu, Frances; Cambron, Emma; Baldwin-Burnett, Anne; Krakow, Jessica; Smejkal, Gary B.
Abstract : Integral membrane proteins play key biological roles in cell signaling, transport, and pathogen invasion. However, quantitative clinical assays for this critical class of proteins remain elusive and are generally limited to serum-soluble extracellular fragments. Furthermore, classic proteomic approaches to membrane protein analysis typically involve proteolytic digestion of the soluble pieces, resulting in separation of intra- and extracellular segments and significant informational loss. In this paper, we describe the development of a new method for the quantitative extraction of intact integral membrane proteins (including GPCRs) from solid metastatic ovarian tumors using pressure cycling technology in combination with a new (ProteoSolve-TD) buffer system. This new extraction buffer is compatible with immunoaffinity methods (e.g., ELISA and immunoaffinity chromatography), as well as conventional proteomic techniques (e.g., 2D gels, western blots). We demonstrate near quantitative recovery of membrane proteins EDG2, EDG4, FASLG, KDR, and LAMP-3 by western blots. We have also adapted commercial ELISAs for serum-soluble membrane protein fragments (e.g., sVEGFR2) to measure the tissue titers of their transmembrane progenitors. Finally, we demonstrate the compatibility of the new buffers with immunoaffinity enrichment/mass spectrometric characterization of tissue proteins.